Cooperation Model for the Development of Whale Shark Tourism in Labuhan Jambu Village, Sumbawa Regency - Fauziah, Dwi Nur; Supryadi, Didy Ika; Furqan, Lalu Muhammad (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the collaboration patterns among stakeholders (government, local community, private sector, academia, and media) in developing the whale shark tourism destination using the pentahelix model approach. This research employed a descriptive qualitative method, with data collected through in-depth interviews, observations, and document analysis. The findings reveal that the pentahelix collaboration has been established, although the roles and contributions of each stakeholder differ. The government plays a role in regulatory formulation, infrastructure provision, and tourism promotion; the local community actively manages and guides tourism activities; the private sector contributes through tourism services and tour packages; academia is engaged in research, community service, and student field programs; while the media supports promotion and public education. This collaboration supports the implementation of Community-Based Tourism (CBT), positioning the local community as the main actor, yet still faces challenges such as limited management capacity, suboptimal regulations, and lack of fully integrated coordination among stakeholders. This study emphasizes that the development of whale shark tourism in Labuhan Jambu Village requires continuous strengthening of pentahelix collaboration to maintain a balance between economic, socio-cultural, and ecological interests.